2016
DOI: 10.1063/1.4960702
|View full text |Cite
|
Sign up to set email alerts
|

Elastic aging from coexistence and transformations of ferroelectric and antiferroelectric states in PZT

Abstract: Materials undergoing antiferroelectric/ferroelectric (AFE/FE) transitions are studied for possible applications that exploit the large volume, charge and entropy differences between the two states, such as electrocaloric cooling, energy storage, electromechanical actuators. Though certain compositions of PbZr1−xTixO3 (PZT) codoped with La and Sn may withstand millions of electrically induced AFE/FE cycles, in other cases few thermally induced cycles and room temperature aging may cause noticeable changes in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Remarkable is also the fact that this type of damage can be totally healed by quick annealing to 800–900 K, even in high vacuum [6,7], at least over a time scale of a few years, presumably before microcracks nucleate. It has also been shown that these phenomena are peculiar of the long term coexistence of FE and AFE domains, by inducing a total stability through doping with 2% La, which transforms the FE phase into incommensurate AFE [8]. In view of their reversibility after relatively mild annealing, the most likely origin of these phenomena is clustering of VnormalO at the FE/AFE interfaces, but a mechanism to explain the large softening has not been proposed [6,7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkable is also the fact that this type of damage can be totally healed by quick annealing to 800–900 K, even in high vacuum [6,7], at least over a time scale of a few years, presumably before microcracks nucleate. It has also been shown that these phenomena are peculiar of the long term coexistence of FE and AFE domains, by inducing a total stability through doping with 2% La, which transforms the FE phase into incommensurate AFE [8]. In view of their reversibility after relatively mild annealing, the most likely origin of these phenomena is clustering of VnormalO at the FE/AFE interfaces, but a mechanism to explain the large softening has not been proposed [6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that these phenomena are peculiar of the long term coexistence of FE and AFE domains, by inducing a total stability through doping with 2% La, which transforms the FE phase into incommensurate AFE [8]. In view of their reversibility after relatively mild annealing, the most likely origin of these phenomena is clustering of VnormalO at the FE/AFE interfaces, but a mechanism to explain the large softening has not been proposed [6,7,8]. The AFE compositions of PZT have been the object of extensive research [9,10,11,12,13], in order to define that region of the phase diagram and improve the physical properties by doping in view of possible applications exploiting the FE/AFE transition, but the associated fatigue and degradation received little attention.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Also PbZrO 3 stiffens when passing from the untilted or disorderly tilted FE R3m phase to the AFE P bam tilted (a − a − c 0 ) phase, but in that case the stiffening can be explained by the loss of the piezoelectric softening, when passing from the FE to the AFE phase (note 12 of Ref. 26). We believe that, in the case of MAPbI 3 , the stiffening when entering in the O phase has two main causes: the loss of mobility of the MA molecules and the stabilization of shorter and hence stiffer N−H· · ·I bonds.…”
mentioning
confidence: 99%
“…[40] and see note 12 of Ref. [41]; note that in those cases one observes the loss of piezoelectric softening, namely a stiffening, during cooling from the FE to the AFE phase). In the absence of additional instabilities, one can reasonably assume that the softening at the FE transition is totally due to Eq.…”
Section: E Subtraction Of the Background Elastic Constantmentioning
confidence: 95%